The Nexus Between Financial Inclusion and Economic Growth in The Organization of Islamic Cooperation (OIC) Countries - Sulaeman, Sulaeman; Ninglasari, Sri Yayu (INDEF - Institute for Development of Economics and Finance, 2022)
This study aims to examine the relationship between financial inclusion and economic growth in 22 OIC countries from 2005-2018 using a panel regression model, especially the REM model. There are three financial inclusion indicators as independent variables considered in this research: the financial inclusion index, the financial outreach index, and the financial usage index. We use GDP per capita as a proxy measure for economic growth. Using a random effect model (REM), our empirical results show that financial inclusion positively and significantly affects national economic growth in OIC countries. It is proven by all the proxy variables of financial inclusion, i.e., the financial inclusion index, financial outreach index, and financial usage index, positively correlate with the GDP per capita as a proxy for national economic growth. Other empirical results from control variables show that inflation is found significant to decrease OIC's economic growth. Trade also has significant effects on economic growth in OIC countries. Besides, in this study, unemployment has positively effects to increase economic growth in OIC countries. The main hypotheses in this study are accepted. Therefore, it could be concluded that financial inclusion positively contributes to increasing economic growth in Muslim countries. Furthermore, this finding will implicate the government to enhance and promote financial inclusion programs massively and provide access to financial services formally, such as insurance, saving, or credits/financing for the underprivileged community, especially for SMEs in all rural areas in OIC countries.